Impact of design of coronary stents and length of dual antiplatelet therapies on ischaemic and bleeding events: a network meta-analysis of 64 randomized controlled trials and 102 735 patients - Fabrizio D’Ascenzo; Mario Iannaccone; Gaëlle Saint‐Hilary; Maurizio Bertaina; Stefanie Schüpke; Cheol Wahn Lee; Alaide Chieffo; Gérard Helft; Sebastiano Gili; Umberto Barbero; Giuseppe Biondi‐Zoccai; Claudio Moretti; et al. (2017)
The differential impact on ischaemic and bleeding events of the type of drug-eluting stent [durable polymer stents [DES] vs. biodegradable polymer stents vs. bioresorbable scaffolds (BRS)] and length of dual antiplatelet therapy (DAPT) remains to be defined. Randomized controlled trials comparing different types of DES and/or DAPT durations were selected. The primary endpoint was Major Adverse Cardiovascular Events (MACE) [a composite of death, myocardial infarction (MI), and target vessel revascularization]. Definite stent thrombosis (ST) and single components of MACE were secondary endpoints. The arms of interest were: BRS with 12 months of DAPT (12mDAPT), biodegradable polymer stent with 12mDAPT, durable polymer stent [everolimus-eluting (EES), zotarolimus-eluting (ZES)] with 12mDAPT, EES/ZES with <12 months of DAPT, and EES/ZES with >12 months of DAPT (DAPT > 12 m). Sixty-four studies with 150 arms and 102 735 patients were included. After a median follow-up of 20 months, MACE rates were similar in the different arms of interest. EES/ZES with DAPT > 12 m reported a lower incidence of MI than the other groups, while BRS showed a higher rate of ST when compared to EES/ZES, irrespective of DAPT length. A higher risk of major bleedings was observed for DAPT > 12 m as compared to shorter DAPT. Durable and biodegradable polymer stents along with BRS report a similar rate of MACE irrespective of DAPT length. Fewer MI are observed with EES/ZES with DAPT > 12 m, while a higher rate of ST is reported for BRS when compared to EES/ZES, independently from DAPT length. Stent type may partially affect the outcome together with DAPT length.